Copper-Nanocoated Ultra-Small Cells in Grain Boundaries Inside an Extinct Vent Chimney - Takamiya, Hinako; Kouduka, Mariko; Furutani, Hitoshi; Mukai, Hiroki; Nakagawa, Kaoru; Yamamoto, Takushi; Kato, Shingo; Kodama, Yu; Tomioka, Naotaka; Ito, Motoo; Suzuki, Yohey (Frontiers in Microbiology, 2022)
Chemosynthetic organisms flourish around deep-sea hydrothermal vents where energy-rich fluids are emitted from metal sulfide chimneys. However, microbial life hosted in mineral assemblages in extinct chimneys lacking fluid venting remains largely unknown. The interior of extinct chimneys remains anoxic where the percolation of oxygenated seawater is limited within tightly packed metal sulfide grains. Given the scarcity of photosynthetic organics in deep seawater, anaerobic microbes might inhabit the grain boundaries energetically depending on substrates derived from rock-water interactions. Here, we report ultra-small cells directly visualized in grain boundaries of CuFeS2 inside an extinct metal sulfide chimney from the southern Mariana Trough. Nanoscale solid analyses reveal that ultra-small cells are coated with Cu2O nanocrystals in grain boundaries enriched with C, N, and P. In-situ spectroscopic and spectrometric characterizations demonstrate the distribution of organics with amide groups and a large molecular organic compound in the grain boundaries. We infer that the ultra-small cells are anaerobes, because of the fast dissolution of Cu2O nanocrystals in oxygenated solution. This Cu2O property also excludes the possibility of microbial contamination from ambient seawater during sampling. Our results support the potential existence of photosynthesis-independent microbial ecosystems in grain boundaries in submarine metal sulfides deposits on the early Earth.